Study of the state of health in the conditions of constant numerous transitional and intermediate stages - Chovhaniuk, O.; Bashkirova, K.; Meleha, K.; Yakymenko, V. V.; Якименко, Володимир Вікторович (My University, 2023)
Aims: To explore the impact of transitional and intermediate stages on physical, mental, and social health. Methodology: A descriptive cross-sectional approach was used. There was no analysis carried whatsoever. Results: Life changes such as marriage, divorce, and retirement affect physical health in different ways, influenced by factors such as marital satisfaction and stress management. Divorce can cause emotional distress, and access to healthcare is critical to managing stress. Retirement can reduce stress but can lead to health risks if it leads to social isolation. Mental health is affected at all stages of life, from academic stress in early adulthood to mid-life crises in middle age and existential rumination in later life. Social determinants of health, such as education, marriage decisions, and career change, are influenced by socioeconomic status, income, and access to health care. Aging people are more affected by income, health care, and support systems. Global events can disrupt access to employment and healthcare, emphasising the interplay of social determinants and life changes. In 2023, the world's population reaches 8.045 billion, of which 25% are aged 0-14 years, 65% are aged 15-64 years and 10% are aged 65+. This age distribution presents challenges and opportunities, requiring investment in education, health and social services for young people, support for the working-age population, and specialised care and resources for older people. Scientific Novelty: Exploring the dynamics of health within a continuum of numerous transitional
Keywords: Health Assessment; Transitional Stages; Intermediate Conditions; State of Health; Constant Monitoring; Study Research